The Uneven Returns of Transparency in Voluntary Nonfinancial Disclosures. (March 2023) - Andrus, Joel L.; Callery, Patrick J.; Grandy, Jake B.
Voluntary nonfinancial disclosures are an increasingly relevant element of corporate sustainability strategies. Despite their importance, research is conflicted on how the transparency of such disclosures affects market and nonmarket outcomes. A possible reason is that transparency consists of multiple dimensions, each of which may be valued differently by market and nonmarket actors. Drawing on insights from attribution theory, we explore the effects that different information traits of voluntary disclosures have on market and nonmarket actors. We suggest that the completeness, clarity, and accuracy of voluntary nonfinancial disclosures affect both market (i.e., market valuation) and nonmarket (i.e., reputation risk) reactions. Using data from the Carbon Disclosure Project, we find that these actors react differently to three distinct dimensions of transparency: completeness, clarity, and accuracy. Our findings highlight the importance of the nuanced relationship between transparency and market and nonmarket actor reactions, which has implications for broader, sustainability-related outcomes.